Telomere length in different metabolic categories: Clinical associations and modification potential. Issue 13 (July 2020) - Khalangot, Mykola; Krasnienkov, Dmytro; Vaiserman, Alexander
Cardio-metabolic disorders, including type 2 diabetes, are known to be associated with accelerated attrition of telomeres, recognized as genetic and biological markers of aging. Some common genetic characteristics were found regarding the presence of shorter telomeres and the development of type 2 diabetes. However, there are conflicting epidemiological reports regarding the association of leukocyte telomeres lengths with type 2 diabetes: not only the causality of such a link remains unclear, but not all researchers acknowledge its existence. The link between current trends in life expectancy of people with type 2 diabetes and the increase in the number of people with type 2 diabetes raises interest in the question of the possibility of drug or life-style-related modification of leukocyte telomeres length. To address the question how leukocyte telomeres lengths are associated with glucose levels in hyperglycemic categories, we examined the correlations between leukocyte telomeres length and fasting plasma glucose and 2 h post-load plasma glucose levels (2hPG). Our data indicate that leukocyte telomeres length is negatively related to 2hPG and the relationship with increasing of fasting plasma glucose may be non-linear. Remarkably, the negative association between leukocyte telomeres length and age was demonstrated in our research only for individuals with normal fasting plasma glucose levels, but not for those with high fasting plasma glucose levels. The nonlinear nature of interactions between age and 2hPG level has been demonstrated by artificial neural networks modeling when investigating the links between leukocyte telomeres length and metabolic syndrome. Thus, it can be assumed that relationships between leukocyte telomeres length and FPG/2hPG levels are not the same, and this distinction can potentially be used in categorization of metabolic disorders. It is possible that these data along with reports of the possibility of modifying leukocyte telomeres length can improve the understanding of present-day epidemiological trends in type 2 diabetes incidence and mortality. Impact statement: Metabolic disorders are known to be associated with accelerated telomere attrition. Their pathophysiological heterogeneity suggests the importance of multiple tests in examining these associations. However, oral glucose tolerance test (OGTT) has rarely been performed in such studies to date. There are few studies aimed at determining leukocyte telomere length (LTL) in different categories of impaired glucose tolerance (IGT), and those that do exist do not take into account the impaired fasting glucose (IFG)/IGT categorization. Therefore, we believe our study, when the OGTT was used, is important to the field. This testing made it possible to determine whether LTLs are associated with glucose levels in different hyperglycemic categories. Our data indicate that relationships between LTLs and IFG/IGT levels are not the same. This distinction can potentially be used in categorization of metabolic disorders and in determining the effectiveness of interventions aimed at treating diabetes and other metabolic abnormalities.